Emotional education (Journal of Parents and Teachers, 2012)
Emotional education is an educational approach that gives answers to social needs that are not attended enough in the key academic areas: anxiety, stress, depression, violence consumption of drugs, behavior of risk, etc. It is necessary to prepare people to confront the challenges of life in a way in which they have more probabilities to succeed.  Emotional education intends to develop emotional competences. Emotional competences are basic type of competences in human life among which we can find emotional conscience, emotional regulation, emotional autonomy and life competences for well-being. Emotional competences develop with continuous training that lead into daily training sessions for life. In this paper, there are presented some examples and suggestions for training theses competences.
Keywords: Affectivity and feeling; Emotional education; Emotional competence; Emotional intelligence